1991
DOI: 10.1063/1.104415
|View full text |Cite
|
Sign up to set email alerts
|

Generation of diamond nuclei by electric field in plasma chemical vapor deposition

Abstract: Generation of diamond nuclei has been realized on a silicon mirror surface in plasma chemical vapor deposition. Prior to the normal diamond growth process, a predeposition process of several minutes duration was introduced in which a high methane fraction in the feed gas was used and in which a negative bias voltage was applied to the substrate. This resulted in an enormous enhancement of the generation of diamond nuclei. For the onset of diamond nucleation the minimum voltage was −70 V and the minimum methane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
164
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 583 publications
(172 citation statements)
references
References 3 publications
2
164
1
1
Order By: Relevance
“…Another widely known method is the Bias Enhanced Nucleation (BEN) method [104] which employs an in situ surface bombardment under an applied negative bias on a conductive substrate. The applied electric field increases the ionization degree of the neutral gas molecules, the energy of the ions and the surface ion bombardment rate.…”
Section: Effect Of Substrate Pre-treatment On Diamond Nucleationmentioning
confidence: 99%
“…Another widely known method is the Bias Enhanced Nucleation (BEN) method [104] which employs an in situ surface bombardment under an applied negative bias on a conductive substrate. The applied electric field increases the ionization degree of the neutral gas molecules, the energy of the ions and the surface ion bombardment rate.…”
Section: Effect Of Substrate Pre-treatment On Diamond Nucleationmentioning
confidence: 99%
“…This approach, however, requires an appropriate substrate material and an efficient nucleation method. The latter is available since the bias enhanced nucleation (BEN) process has been introduced [5]. With iridium Ohtsuka et al [6] found a material which provides an ideal substrate for heteroepitaxial diamond deposition ten years ago.…”
Section: Introductionmentioning
confidence: 99%
“…The Little Effect [1] is therefore different from the ElSayed Effect [22] (that photo-excited orbital states can couple strongly with electron spins to cause intersystem crossing nonadiabatically), but here on the basis of the Little Effect the dense phonons, rotons and magnons in the quantum fluids are determined to affect orbital dynamics adiabatically, via the lone electrons of complexation binding antibonding sp 2 orbitals of the graphitic carbon, causing spin interaction with the ring current within the graphitic structures for destabilizing and lowering the bond order of the graphitic structures. Such catalytic activated pi bond cleavage is consistent with electric charge activated diamond nucleation (biased enhanced nucleation) of Yugo [26]. Negatively charging and polarizing carbon atoms or carbanion formation [26] also facilitate the breakage of bosonic bonding of graphitic and carbyne precursors, just as the radicals serve the role of electrons in occupying antibonding orbitals for graphitic decomposition during biased enhanced nucleation BEN.…”
Section: The Resolution Of the Diamond Problemmentioning
confidence: 62%